Micromorphological characteristics of soils in the Chernevaya taiga (Western Siberia, Russia) - Abakumov, Evgeny V.; Nizamutdinov, Timur; Lapidus, Alla; Istigechev, Georgy I.; Loyko, Sergey V. (Geosciences)
The Chernevaya taiga is a unique ecosystem formed under the influence of a complex of geogenic and bioclimatic factors located in the foothill border of the southeastern part of Western Siberia. The combination of local climatic conditions and the composition of parent material led to the formation of specific soil conditions on the territory of these habitats. The soils of the Chernevaya taiga have unique morphogenesis. They have a thick podzolized horizon and are fertile, unlike the typical soils of the oligotrophic pine forests of Siberia; however, the microstructure of these soils is poorly studied. The purpose of the research is to analyze the micromorphological organization and microstructure of three types of soils in Western Siberia (two typical soils from the Chernevaya taiga (Greyzemic Phaeozem (Albic) and Albic Stagnic Luvisol (Ochric)) and one from oligotrophic pine stand (Eutric Protoargic Arenosol)). It was found that the soils of the Chernevaya taiga differ greatly from the background (zonal) soils of the region on both the macro- and microlevels. In the Phaeozems and Luvisols of the Chernevaya taiga, there are actively formed organomineral aggregates and the quantity of porous media is more than 50%. At the bottom of the podzolized part of the soil profiles, we noted illuvial processes and a sharp change in the type of microstructure. The presence of pyrogenic materials (charcoal) and coprolitic (vermicular) materials in the humus-accumulative horizon indicates a high rate of material transformation and high biological activity and bioturbation in the soil. The skeleton part of the Chernevaya taiga soils is represented by a quartz–feldspar base with an admixture of sericite; augite; biotite; and a minimal admixture of tourmaline, zircon, and glauconite.